(untitled) (Asian Journal of Plant Biology, 2022)
This study investigated the microorganisms associated with the spoilage of tomato (Lycopersicum esculentum) obtained from two markets in Jahun town, Jahun Local Government in Jigawa State, Nigeria. A total of five species of bacteria were isolated and identified viz: Bacillus subtilis, B. aureus, Escherichia coli, Klebsiella aerogenes and Staphylococcus aureus. The most prevalent bacterial isolate was Bacillus subtilis with 24% and was found in all samples from the two markets. Klebsiella aerogenes was the least prevalent isolate with 0.8% and was found in samples from Jahun Central Market only. The fungal isolates were Penicilium notatum, Mucor mucido and Aspergillus niger. Whereas, Mucor mucido was the most prevalent with 26.4% and was found in fruit samples from all the markets, Penicillium notatum had the least prevalence of 7.3% and occurred both in Jahun Central and Kabala Markets. The mean microbial count ranges were 10 to 40 × 104 CFU/g for Jahun Central Market and 5 to 30 × 104 CFU/g Kabala Market. The presence of toxin producing fungi Aspergillus niger, which are capable of causing food poisoning as well as some bacterial isolates raises concern over public health risks that may be associated with the consumption of spoiled tomato fruits.